US Food and Drug Administration review of statistical analysis of patient-reported outcomes in lung cancer clinical trials approved between January, 2008, and December, 2017. Issue 10 (October 2019) - Fiero, Mallorie H; Roydhouse, Jessica K; Vallejo, Jonathon; King-Kallimanis, Bellinda L; Kluetz, Paul G; Sridhara, Rajeshwari
Summary: With the advent of patient-focused drug development, the US Food and Drug Administration (FDA) has redoubled its efforts to review patient-reported outcome (PRO) data in cancer trials submitted as part of a drug's marketing application. This Review aims to characterise the statistical analysis of PRO data from pivotal lung cancer trials submitted to support FDA drug approval between January, 2008, and December, 2017. For each trial and PRO instrument identified, we evaluated prespecified PRO concepts, statistical analysis, missing data and sensitivity analysis, instrument completion, and clinical relevance. Of the 37 pivotal lung cancer trials used to support FDA drug approval, 25 (68%) trials included PRO measures. The most common prespecified PRO concepts were cough, dyspnoea, and chest pain. At the trial level, the most common statistical analyses were descriptive (24 trials [96%]), followed by time-to-event analyses (19 trials [76%]), longitudinal analyses (12 trials [48%]), and basic inferential tests or general linear models (10 trials [40%]). Our findings indicate a wide variation in the analytic techniques and data presentation methods used, with very few trials reporting clear PRO research objectives and sensitivity analyses for PRO results. Our work further supports the need for focused research objectives to justify and to guide the analytic strategy of PROs to facilitate the interpretation of patient experience.